Guns, Youth Violence, and Social Identity in Inner Cities - Fagan, Jeffrey A. (1998)
While youth violence has always been a critical part of delinquency, the modern epidemic is marked by high rates of gun violence. Adolescents in cities possess and carry guns on a large scale, guns are often at the scene of youth violence, and guns often are used. Guns play a central role in initiating, sustaining, and elevating the epidemic of youth violence. The demand for guns among youth was fueled by an "ecology of danger," comprising street gangs, expanding drug markets with high intrinsic levels of violence, high rates of adult violence and fatalities, and cultural styles of gun possession and carrying. Guns became symbols of respect, power, identity, and manhood to a generation of youth, in addition to having strategic value for survival. The relationship between guns and youth violence is complex. The effects of guns are mediated by structural factors that increase the youth demand for guns, the available supply, and culture and scripts which teach kids lethal ways to use guns